Impacto de los instrumentos de promoción de la innovación orientada al sector productivo: El caso de ANII en Uruguay - Daniel Bukstein; Elisa Hernández; Ximena Usher (Estudios de Economía, 2018)
– The goal of this paper is to evaluate the impact of the innovation promotion programs carried by the National Research and Innovation Agency (ANII). A combination of non-experimental methods was used to quantify the effects of public support to innovation in three dimensions of the firms' behavior: innova - tion investment, innovation results and economic performance. The results show evidence of crowding-in of public support to innovation. Also, beneficiaries of the programs show larger probability of successfully introducing new products and processes. We do not find impact in the economic performance indicators of the firms.
Keywords: D22; O38; C21; H43; H54; 330; Impact evaluation; innovation; ANII; Uruguay